Parkinsonian monkeys with prior levodopa‐induced dyskinesias followed by fetal dopamine precursor grafts do not display graft‐induced dyskinesias. Issue 3 (29th August 2016) - Kordower, Jeffrey H.; Vinuela, Angel; Chu, Yaping; Isacson, Ole; Redmond, D. Eugene
ABSTRACT: Clinical trials testing the hypothesis that fetal dopamine grafts would provide antiparkinsonian benefit in patients who had already developed side effects from their long‐term use of L‐dopa revealed, in some cases, the presence of dyskinesias even in the absence of L‐dopa. The form, intensity, and frequency of these dyskinesias were quite variable, but their manifestation slowed the clinical development of cell replacement therapies. Rodent models of graft‐induced dyskinesias (GIDs) have been proposed, but their accuracy in modeling GIDs has been questioned because they usually require amphetamine for their presentation. The present study attempted to model GIDs in parkinsonian monkeys and, for the first time, to test the effect of grafts on previously dyskinetic monkeys. Toward this end, monkeys were rendered parkinsonian with n‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) and dyskinetic with levodopa. They then received intraputamenal grafts of fetal dopaminergic cells, control cerebellar cells, or vehicle bilaterally and were studied for 18 months. Dopaminergic cells were grafted in a manner designed to produce either "hot spot" or "widespread" striatal innervation. Although levodopa‐induced dyskinesias could be elicited postoperatively, GIDs were never observed in any animal at any time after grafting. Grafted monkeys were also challenged with levodopa but did not show any greater responses to these challenges than before grafting. These studies support the development of future dopamine neuron cell transplantation therapy‐based approaches, indicating that in relevant primate models with appropriate cell preparation methodology, with successful graft survival and putamenal dopamine innervation, there is no evidence of graft‐induced dyskinesias. J. Comp. Neurol. 525:498–512, 2017. © 2016 Wiley Periodicals, Inc. Abstract : We attempted to model the "off‐medication" dyskinesias seen clinically in patients with Parkinson's disease following fetal ventral midbrain grafts by implanting fetal dopaminergic allografts in levodopa‐dyskinetic parkinsonian monkeys using focal and widespread grafting patterns. No off‐medication dyskinesias were ever observed in any monkey over an 18‐month postgrafting period despite excellent graft survival and dopaminergic innervation.